Does government export assistance moderate strategic capabilities and export performance manufacturing SMEs in Malaysia? / Siti Normah Awang Tuah… [et al.] - Awang Tuah, Siti Normah; Mat Saad, Rosfadzimi; Mohamed, Noor Azzura; Mohd Yusof, Aini Qamariah; Hasin, Hanafiah; Johari, Yang Chik; Jamil, Anita (2023)
The contribution of Small and Medium Enterprises (SMEs) in increasing the national income of Malaysia is very significant. They not only help Multi-National Companies (MNCs) move forward but also become the backbone that supports enhancing the progress of Malaysia’s Exports. Although their strategic capabilities seem increasingly significant in increasing their export performance, they always need the government's help to ensure they survive in export activities. Therefore, it is also believed that government export assistance is an important resource that supports the exporters in increasing their export performance. This study aims to provide insights to policymakers in designing development programs to promote manufacturing products of SMEs in international business. Thus, it is crucial to test whether the relationship between strategic capabilities and export performance is strengthened with the usage of government export assistance (moderator). Results showed that the moderator strengthens the relationship between strategic capabilities and export performance if the SMEs use financing assistance provided by the government. Specifically, the financing assisted the manufacturing SMEs innovation capability and marketing capability in enhancing export performance. With the assistance from the government and policy makers through their programs and funding allocation, Malaysian SME manufacturing companies should be more competent and capable in growing their export performance. This study is originally focusing on Malaysian manufacturing SMEs usage of government assistance program (financial), thus future research can take a step further by studying types of financial assistance used by manufacturing SMEs to gain deeper understanding of the value creation of government export assistance programs to improve their strategic capabilities and increase export performance.